REPRESENTATION OF THE FATHER FIGURE IN PARENTING IN THE LATEST INDONESIAN NOVEL: A STUDY OF FATHER'S MASCULINITY - Nadia Sutra Lismi; Anwar Efendi (Literature and Literacy, 2023)
Discussions about masculinity, in general, will be associated with certain stereotypes of masculinity. This study aimed to describe the representation of masculinity-fatherhood in the latest Indonesian novels. This research was descriptive qualitative research using the fatherhood theory by Asy'ari and Ariyanto. Data sources were several novels entitled My Father (Not) a Liar (Tere Liye), Ayah (Andrea Hirata), Saturday with Father (Adhitya Mulya), and Father Loves Without End (Kirana Kejora). The steps of data analysis in this study used the technique stated by Miles, et al (2014: 10-12) which included collecting data by means of repeated reading of the novel manuscript and then marking/coding the data found, condensation, and categorizing, analyzing, and drawing a conclusion. The results of the research showed that there was a male role as a son, husband, or father who participated in the domestic sphere while still making or showing his masculine side who show with communication, responsibility, interaction with children, teaching methods, and supervisory roles. The conclusion was father's involvement in the parenting role was a manifestation of emotional closeness, the father's accessibility, and responsibility in various aspects. This was a form of support for men who are more pro-feminist where men can share roles in various aspects. This paternal role was also shown as a form of crossing over between masculine and feminine gender roles, which was a reaction to the hegemony of masculinity as a form of effort to eradicate the dominant father's role in a family.